PENGARUH PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL MODERASI TRANSPARANSI - Arif Fajar Kurniawan; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2017)
The goal of this research is to examine the effect of tax avoidance on firm value and how if company transparency roled as moderating variable. On this research, it uses firm value as dependent variable and Tobin’s Q as it measures. Tax avoidance represents the independent variable as measured by BTD. The moderating variable is company transparency and use Corporate Governance Self Asseeement Checklist released by Forum for Corporate Governance in Indonesia as it measured. This research also use four control variables.            There are 135 non-financial companies listed in Indonesia Stock Exchange which have financial report on 2016 period as the sample of this researh. Multiple regression analysis is choosen to be used in this research.            The result of the research shows that the independent variable, tax avoidance, has positive effect on firm value but negative on agency cost. The transparency succeed to moderate the effect of tax avoidance on firm value become positive effect.